Full genomic amplification and subtyping of influenza A virus using a single set of universal primers - Inoue, Emi; Wang, Xiaofeng; Osawa, Yoshiaki; Okazaki, Katsunori (Microbiology and immunology, 2010)
Influenza A virus has eight-segmented RNA molecules as a genome and, among all strains of the virus, both ends of each segment have 13 and 12 nucleotide sequences conserved. In the present study, a simple RT-PCR method to amplify all eight segments of the virus and determine the HA and NA subtype using a single primer set based on the conserved terminal sequences has been established. This method is also capable of detecting subgenomic defective interfering RNA of the influenza A virus. Since the primers used here cope with each and every RNA segment of influenza A virus, this simple RT-PCR method is valuable not only for cloning each gene of the virus, but also for identifying subtypes, including subtypes other than 16 HA and 9 NA subtypes.